2016
DOI: 10.1364/ao.55.004706
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of drying paint coatings by dynamic speckle and holographic interferometry measurements

Abstract: In this work we implemented dynamic speckle and holographic interferometry techniques to characterize the drying process of solvent-based paint coatings. We propose a simple way to estimate drying time by measuring speckle activity and incrementally fitting experimental data through standard regression algorithms. This allowed us to predict drying time after about 20-30 min of paint application, which is fast compared to usual times required to reach the so-called tack-free state (≈2  h). In turn, we used holo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This means that over the long-term, DLS when monitored is a better sensor than the traditional DLS with high time-rate (10 fps); and also better than the weighing process that could be considered as the ‘gold standard’. The monitoring of drying paint using the traditional fps is usually restricted to the first minutes [ 20 , 23 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that over the long-term, DLS when monitored is a better sensor than the traditional DLS with high time-rate (10 fps); and also better than the weighing process that could be considered as the ‘gold standard’. The monitoring of drying paint using the traditional fps is usually restricted to the first minutes [ 20 , 23 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of the processes are critical in DLS, and adjustments are required in the setup, as well as in the choice of the best image processing method. In colloids, which is the case of paintings, the literature discusses DLS and paint drying [ 20 , 21 , 22 , 23 ], where the level of activity of the scatterers greatly varies from the moment the ink is applied, with high levels of volatilization until the end of the drying process. Thus, a method of monitoring the process without compromising the observation of the phenomenon deserves to be evaluated and tested.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results presented here widen the scope of both dynamic speckle and DHI methods regarding characterization of dynamic phenomena, due to the possibility of correlating SA evolution with interferometric variations. 22,23 2 Experimental Details We performed simultaneous measurements of the drying process of a solvent-based paint coating by acquiring holographic images and also dynamic speckle images (with a second digital camera) in order to compare the SA evolution extracted from the holograms with that observed directly from speckle images. The drying process of paint coatings is a typical and predictable study case in the field of dynamic speckle, since the observed SA is known to decay smoothly as a function of time.…”
Section: Introductionmentioning
confidence: 99%